The Cost Efficiency of Wild Dog Conservation in South Africa - LINDSEY, P. A.; ALEXANDER, R.; DU TOIT, J. T.; MILLS, M.G.L. (Conservation biology, 2005)
Aside from Kruger National Park, no other suitable reserves of sufficient size exist in South Africa that will hold a viable population of wild dogs (Lycaon pictus). Consequently, conservation efforts have been focused on creating a metapopulation through a series of wild dog reintroductions into isolated fenced reserves. Additional potential exists for conserving wild dogs on private ranch land. Establishing the metapopulation was an expensive process, accounting for approximately 75% of the US$380,000 spent on wild dog conservation in South Africa during 1997-2001. The principal goal of the metapopulation project was to reduce the risk of catastrophic population decline. Now that this has been achieved, we developed a uniform cost-efficiency index to estimate the cost efficiency of current and potential future conservation strategies in South Africa. Conserving wild dogs in large protected areas was predicted to be the most cost-efficient conservation strategy (449 packs/$100,000 expenditure). Establishing the metapopulation has been less cost efficient (23 packs/$ 100,000), and expansion of the metapopulation was predicted to be even less cost efficient if predation by wild dogs results in additional costs, as is to be expected if private reserves are used for reintroductions (3-13 packs/$100,000). Because of low logistical costs, conserving wild dogs in situ on private ranch land was potentially more cost efficient than reintroducing wild dogs (14-27 packs/$100,000). We recommend that donor funding be used to reintroduce wild dogs into transfrontier parks, when they are established, to maintain the existing metapopulation and to establish conservation programs involving wild dogs on private ranch land. Investing in the expansion of the metapopulation should be limited to state-owned nature reserves willing to carry predation costs without compensation.